Pengaruh Family Quality Time terhadap Akhlak Siswa di SMPIT Al-Istiqomah Global School Karawang - Indah Fasikha Ayuningsih; Akil Akil; Jaenal Abidin (ISLAMIKA, 2022)
Parents have a great responsibility in guiding, directing and being responsible for creating a religious family environment. Therefore, the role of parents is very decisive in the formation of pious children. This study aims to determine the effect of family quality time on the morals of students at SMPIT Al-Istiqomah Global School Karawang. The population in this study were students of SMPIT Al-Istiqomah Global School Karawang. The sampling technique of this study used a random sampling technique consisting of 45 samples. The results of the descriptive analysis of the family quality time variable have a value interval of 63-75 for 35 students, with a percentage of 77.60% in the very good category. While the results of the descriptive analysis of the moral variable there is an interval of 66-76 values in 23 students, with a percentage of 51.10% in the very good category. The results of the t-test showed that tcount > ttable (7.895 > 2.016) then Ho was rejected statistically significant, from the t-test results the significance value was less than 0.05 (0.000 < 0.005) meaning that there was a close influence between family quality time on student morale. at SMPIT Al-Istiqomah Global School Karawang.